2008
DOI: 10.2139/ssrn.1115326
|View full text |Cite
|
Sign up to set email alerts
|

Migrants as Second-Class Workers in Urban China? A Decomposition Analysis

Abstract: In urban China, urban resident annual earnings are 1.3 times larger than long term rural migrant earnings as observed in a nationally representative sample in 2002. Using microsimulation, we decompose this difference into four sources, with particular attention to path dependence and statistical distribution of the estimated effects: (1) different allocation to sectors that pay different wages (sectoral effect); (2) hourly wage disparities across the two populations within sectors (wage effect); (3) different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…24 Using the 2005 and 2010 samples of the China Urban Labor Study, Giles et al (2011) show that migrants are 43 percent less likely to have pension contributions through the employer. In a decomposition study of wage differences in urban workplaces, Démurger et al (2009) compare the explained variance of hukou status as compared to education level. They find that education attainment was the major driver of wage disparities by pre-determining the sector of employment for rural and urban hukou-holders.…”
Section: Extensionsmentioning
confidence: 99%
“…24 Using the 2005 and 2010 samples of the China Urban Labor Study, Giles et al (2011) show that migrants are 43 percent less likely to have pension contributions through the employer. In a decomposition study of wage differences in urban workplaces, Démurger et al (2009) compare the explained variance of hukou status as compared to education level. They find that education attainment was the major driver of wage disparities by pre-determining the sector of employment for rural and urban hukou-holders.…”
Section: Extensionsmentioning
confidence: 99%
“…For example, Meng and Zhang (2001) find that education increases the probability of rural migrants of obtaining a white-collar job. A recent study by Demurger et al (2009) finds that the sectoral difference is not as important as the differences driven by educational attainment. Gagnon et al (2009) first point out the substantial differences in comparing the rural migrants, urban migrants, and urban residents by decomposing the migration effect and hukou effect.…”
mentioning
confidence: 94%
“…Studies on the determinants of selection into different occupational sectors (Meng and Zhang, 2001;Demurger et al, 2009;Gagnon et al, 2009) have shown that both education and experience play an important role in the occupational segregation between rural migrants and urban residents. 11 Nonetheless, De Brauw and Giles (2006) point out that many cities have reserved some occupational categories for registered urban residents and that there is a segregation of rural residents into unskilled service and construction sectors or other relatively low-skilled jobs that are unwanted by the urban residents.…”
mentioning
confidence: 99%
“…Despite China's strict household registration (hukou) system that remains in effect to control labor migration, the rural migrants in urban cities increased from about 30 millions in 1989, to 62 millions in 1993, and further to 145 millions in 2010 (Demurger et al, 2009;National Bureau of Statistics, 2010). Also well documented is the important role of social networkfamily, friends, and acquaintances -in the Chinese rural-urban migration.…”
Section: Introductionmentioning
confidence: 99%
“…Given its negative wage effects, the widespread use of social networks in the job search process could thus contribute to the increase in the withingroup inequality among rural migrants and hence overall inequality in China. 4 Similarly, due to its significant wage impacts, the use of informal job search method could also play a potentially important role in understanding between-group inequality such as the wage gap between rural migrants and urban residents (e.g., Meng and Zhang, 2001;Demurger et al, 2009), or between rural migrants and urban migrants (Messinis, 2013). 5 Second, together with other empirical evidence obtained in the literature, our paper could help to characterize some important features of China's labor market and economy.…”
Section: Introductionmentioning
confidence: 99%